The Role of Incentive Spirometry in Primary Spontaneous Pneumothorax - Rabbinu R Pribadi; Gurmeet Singh; Cleopas M Rumende (Acta Medica Indonesiana, 2016)
Pneumothorax is the presence of air in the pleural space. Its management consists of noninvasive and invasive therapies and it is determined based on clinical manifestations, type and size of pneumothorax. We present a case of a patient with diagnosis of primary spontaneous pneumothorax treated with incentive spirometry (noninvasive therapy). A 20 year old man came to respirology clinic with chief complaint of shortness of breath. He was recently diagnosed with left pneumothorax based on previous chest X-ray in another health care facilities and was advised to undergo tube thoracostomy but he refused the procedure. On physical examination, vital signs were normal. Chest X-ray showed 33% of pneumothorax or 1.2 cm. He was asked to perform incentive spirometry therapy at home. During 12 days of therapy, shortness of breath slowly disappeared and on repeated chest X-ray, it showed minimal pneumothorax in the left upper hemithorax. Noninvasive treatment such as incentive spirometry can be considered in patient with minimal symptoms and no signs of life-threatening respiratory distress.